2021
DOI: 10.3390/nu13062053
|View full text |Cite
|
Sign up to set email alerts
|

“Just So You Know, It Has Been Hard”: Food Retailers’ Perspectives of Implementing a Food and Nutrition Policy in Public Healthcare Settings

Abstract: Mandated policies to improve food environments in public settings are an important strategy for governments. Most Australian governments have mandated policies or voluntary standards for healthy food procurement in healthcare facilities, however, implementation and compliance are poor. A better understanding of the support required to successfully implement such policies is needed. This research explored food retailers’ experiences in implementing a mandated food and nutrition policy (the Policy) in healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…These include implementation toolkits or manuals, self-evaluation tools, scalable sample recipe ideas, training to improve staff culinary skills, newsletter and contract templates, access to nutrition analysis software, or a database listing healthy, compliant products. For example, participants in the Law et al study identified a “centralised provision of lists or databases of classified foods and drinks to reduce duplication of effort and the technical burden,” 41 because food providers noted, “You can’t go and find out this stuff yourself so easily.” 70 Importantly, such tools and resources need to be tested, user friendly, and up to date.…”
Section: Results Of Thematic Synthesis Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…These include implementation toolkits or manuals, self-evaluation tools, scalable sample recipe ideas, training to improve staff culinary skills, newsletter and contract templates, access to nutrition analysis software, or a database listing healthy, compliant products. For example, participants in the Law et al study identified a “centralised provision of lists or databases of classified foods and drinks to reduce duplication of effort and the technical burden,” 41 because food providers noted, “You can’t go and find out this stuff yourself so easily.” 70 Importantly, such tools and resources need to be tested, user friendly, and up to date.…”
Section: Results Of Thematic Synthesis Of Findingsmentioning
confidence: 99%
“…Although a positively framed policy and implementation plan are advantageous in lessening negative perceptions of change, accepting change requires building rapport with food providers, contingent on existing and new positive relationships in a workplace. As Law et al noted, “the trust built with the PHD [public health dietitian] meant [food providers] openly discussed their experiences, from a position of acceptance, not resistance.” 41 Studies frequently identified open and clear communication between stakeholders as facilitating the shift from food providers’ resistance to acceptance, for example, by “making sure that everybody knew all along the way what we were doing, what was expected of them and of their team.” 53 Regular communication efforts originating from governmental bodies, senior workplace management, or project champions demonstrate acceptance across organizational levels, and indicate to food providers the leadership’s willingness to work collaboratively to overcome barriers and achieve policy compliance. Green et al highlighted “that a positive relationship and open, frequent communication where both the city and vendor listened to each other’s concerns and worked together to address them was essential to successful implementation.” 52 Furthermore, shared responsibility and a collaborative approach to implementation can mitigate feelings of being disproportionately disadvantaged as a food provider and allows recognition of implementers’ fears, concerns, and barriers (both experienced and perceived) that can create negative perceptions of the policy.…”
Section: Results Of Thematic Synthesis Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous authors have already established that innovation is a means to developing healthy and sustainable foods [ 11 ]. Accessing appropriate food products is an identified challenge for health service food retailers [ 12 ], highlighting the importance of understanding the current and potential food supply of healthy and sustainable food products that are safe and flavoursome.…”
Section: Introductionmentioning
confidence: 99%